Documentation and analysis of reconstruction practices in Haiyan-affected areas - Cruzat, Julius Bryan O.; Aquino, Diocel Harold M.; Germar, Fernando J. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The main objective of this study is to document the reconstruction practices of residents living in non-engineered houses in areas that were severe ly affected by typhoon Haiyan in 2013. The study aims to determine the trends in the practices based on location of the house, socio-economic status of the respondent, and type of hazard present. Using existing manuals for post-di saster reconstruction, the trends in the reconstruction practices were evaluated with regards to its adequacy. Up until the time of this study, the province of Leyte has yet to fully recover from damage brought about by the super typhoon Haiyan (Yolanda). A great number of residents live in houses whose quality is worse compared to its previous state before Haiyan, many of which live in makeshift houses. The study was conducted in the City of Tacloban and municipalities of Palo and Tanauan from February 27 until March 2, 2015. Using a survey form, 106 residents from 7 different barangays were interviewed regarding the specific steps they took to reconstruct their houses and the reasons behind them. Photographs of each household were taken, highlighting the reconstruction practices that were applied. Commentaries on respondents' practices and factors that innuence their practices are given, as well as commentaries on the general state of reconstruction in the sample communities.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Dwellings -- Repair and reconstruction; Typhoons -- Philippines; Typhoon Haiyan, 2013.